The Policy of the Minister of Defense of the Republic of Indonesia Toward the Indonesian Air Force (A Case Study of the Work Environment at the Air Force Material Maintenance Command) - Dwicahyo Satrio Wibowo; Lusi Andriyani; Usni Hasanudin (Al-Makki Publisher, 2026)
This research analyzes the implementation of the Indonesian Minister of Defense's policy on improving the facilities and infrastructure of the Indonesian Air Force, using a case study at the Air Force Materiel Maintenance Command (Koharmatau). As a technical unit that carries out the maintenance function of defense equipment, Koharmatau is in the process of transforming into a digital-based work system through the implementation of the Smart Building concept. The study uses a qualitative approach with a case study method, combining in-depth interviews with key informants, participant observation, and analysis of policy documents and internal unit reports. Data collection was conducted in the Koharmatau environment, Bandung, with a focus on aspects of physical infrastructure, energy management systems, and organizational dynamics. The results show that the policy implementation is running adaptively and gradually through an adaptive incrementalism approach, with initial achievements in the form of a 12% reduction in energy consumption and the implementation of a Building Automation System in priority facilities. However, successful implementation still faces structural obstacles in the form of procurement bureaucracy, limitations of old infrastructure, competency gaps between generations of personnel, and suboptimal coordination between agencies. This research concludes that the effectiveness of the infrastructure modernization policy is highly dependent on the ability to create synergy between technology, human resources, and a holistic transformation of organizational culture.